How has Indigenous Health Research changed in Atlantic Canada over two decades? A scoping review from 2001 to 2020. (June 2021) - White, Tara; Murphy, Kathleen; Branje, Karina; McKibbon, Shelley; Cunsolo, Ashlee; Latimer, Margot; McMillan, Jane; Sylliboy, John; Martin, Debbie
Abstract: Introduction: Indigenous communities across Canada report that transformations in Indigenous health research are needed, where the benefits of research shift intentionally, collaboratively, and with transparency from the researchers directly to Indigenous communities and partners. Despite its challenges and potential for harm, research, if done ethically and with respect and partnership, can be a force for change and will strengthen the efficacy of data on Indigenous Peoples' health and wellbeing. Purpose: To characterize the nature, range, and extent of Indigenous health research in Atlantic Canada, and to identify gaps. Methods: Eleven databases were searched using English-language keywords that signify Indigeneity, geographic regions, health, and Indigenous communities in Atlantic Canada between 2001 and May 2020. All references were reviewed independently by two reviewers. Of the 9056 articles identified, 211 articles were retained for inclusion. Data were extracted using a collaboratively developed data charting form. Results: Indigenous health research in Atlantic Canada has increased over time, covering a diverse range of health topics. The main areas of research included climate change, child and youth health, and food and water security, with the majority of research deriving from Newfoundland and Labrador. Rates of reported community engagement remain relatively low and steady between 2001 and 2020, however there was an increase in researchers seeking Indigenous ethics approvals for such engagement. Conclusions: This scoping review synthesizes 20 years of Indigenous health research in Atlantic Canada. The results indicate that although there are increases in Indigenous ethics approvals, there is more work needed to ensure that Indigenous Peoples lead, design, and benefit from research conducted in their homelands. Highlights: The majority of research undertaken has been with Inuit communities in Labrador. Research undertaken has a predominant focus on climate change/environmental health. There is an increase in authors seeking Indigenous ethics approval. There is little change in community engagement at any point in the research process.